The Organization and Methodology In The Educational Process Of Physical Education - Asatillaevich, Abbasov Bakhadir (Jurnal Teknologi Pendidikan, 2024)
Health, by its very nature, is a person's primary need. The satisfaction of this need, bringing it to an optimal result, is complex, peculiar, often contradictory, indirect in nature and does not always lead to the desired result. This situation is due to a number of circumstances, and first of all, the fact that in our country the population has not yet formed a sufficiently positive motivation to take care of their health.